Moral Responsibility in the Context of Prenatal Testing: What can be Expected? - Lemoine, Marie-Eve (BioéthiqueOnline, 2015)
Authors have suggested that considering the ethical and social aspects of prenatal testing could be seen as an individual responsibility for patients, but no conceptual grounds have been provided for this thesis. I argue that Candace Cummins Gauthier’s account of “moral responsibility as a virtue”, developed as an attempt to reconcile notions of autonomy and community, provides such basis.